Solid Phase Extraction and Separation of Polysaccharides from Marine Plant by Ionic Liquid-Modified Polymers - Zhang, Heng; Tang, Baokun; Ho Row, Kyung (Asian Journal of Chemistry, 2015)
Ionic liquid-modified polymers were applied to the separation of laminarin and fucoidan by solid phase extraction from natural plant sources. The most suitable sorbent for polysaccharide separation was identified from the adsorption behaviour of the targets on different ionic liquid modified polymers. The proper elution solvents for both laminarin and fucoidan were determined from practical tests. The sorbents performed stably and selectively, showing potential applications in the separation of other polysaccharides or other biomacromolecules.